Impact of entrepreneurial orientation dimensions on performance of small enterprises: Do entrepreneurial competencies matter? - Mukaram Ali Khan; Syed Sohaib Zubair; Kashif Rathore; Maryam Ijaz; Sumreen Khalil; Muhammad Khalil (Cogent Business & Management, 2021)
The purpose of this study is to examine the role of entrepreneurial orientation (EO) in determining the enterprise performance (EP) during Covid-19. Moreover, in context of this relationship, the mediating role of entrepreneurial competencies (EC) has also been investigated in influencing the EO and EP connection. This quantitative study employs techniques for operationalizing and quantifying the variables under consideration followed by various statistical operations using SPSS and AMOS in order to test and explore the relationship as proposed in the conceptual framework, using data from 386 small enterprises as sample identified through Systematic random sampling. The analysis revealed that a positive relationship exists among all the constructs directly as well as through the mediator (EC). However, the strongest direct relation existed between risk taking propensity (RTP) and enterprise performance. Moreover, when EC is introduced as the mediator between the dependent and independent variables, again RTP path showed the strongest link. Several governments, particularly in the underdeveloped or developing countries try to support and boost the development of small businesses for the achievement of developmental objectives as well as to address the challenge of unemployment. This research explores both these key components in the context of Pakistan, testing the importance of EO and EC for small businesses. This study also provides the roadmap for policy makers to strengthen small enterprises for better performance.
Keywords: L26; M00; O00; 650; Entrepreneurial orientation; entrepreneurial competencies; enterprise performance; small enterprises